Relationship between emotional intelligence and managerial skills in peruvian accountants (GnosisWisdom, 2024)
Introduction: Emotional intelligence (EI) and managerial skills (MS) are crucial for performance in accounting. In Peru, research is limited, but globalization and digitalization have increased the demand for soft skills, making EI essential for organizational success in the Peruvian socioeconomic context. The objective was to determine the relationship between EI and MS of graduates from the Professional School of Accounting at the National University of Huancavelica (UNH), period 2014-2017. Methodology: This study used a non-experimental transactional correlational design to examine the relationship between EI and MS in 72 graduates. A validated questionnaire with a Cronbach's alpha of 0.88 was used to measure EI dimensions (intrapersonal, interpersonal, and adaptability). Data were analyzed using SPSS software version 25. Results: 66.7% of participants showed a normal level of EI, and 22.2% an elevated level. Spearman's correlation analysis indicated a positive and significant correlation between EI and MS (ρ = 0.775, p < 0.01), suggesting that 69.0% of MS can be explained by EI. The dimensions of adaptability (ρ = 0.749), intrapersonal (ρ = 0.743), and interpersonal (ρ = 0.718) showed significant correlations with MS. Conclusion: The UNH should integrate the teaching of EI into their curricula to better prepare students for the labor market, thereby improving their professional performance and strengthening the accounting sector in Peru.
Keywords: Emotional intelligence; Managerial skill; Accounting; Peru; Correlation